AUTOLOGOUS HAEMOPOIETIC STEM CELL TRANSPLANT IN MS: SHEFFIELD COHORT. Issue 11 (14th October 2015) - Kelsey, P; Bell, SM; Jessop, H; Snowden, JA; Sharrack, B
Abstract : Background: Autologous haemopoietic stem cell transplantation (AHSCT) is an evolving therapy for multiple sclerosis (MS). Here we present the Sheffield experience since 2006. Methods: Retrospective review of MS cases referred for and treated with AHSCT. Toxicity, clinical and radiological outcome were assessed. Results: 14 patients (8 Rapidly evolving severe [REMS], 3 Relapsing Remitting [RRMS], 3 Secondary Progressive [SPMS]) were selected for AHSCT. One patient underwent AHSCT on a clinical trial (data excluded from analysis). Mean age 34.6 years (SD 8.69), median pretreatment EDSS 6.5 (IQR0.5). All had clinically and radiologically aggressive disease, non-responsive to standard treatment. Follow up range was 3 to 96 months. All patients were successfully mobilized, 2 patients progressed only to harvest (1 compliance issues, 1 leg ulcer). All patients were treated according to international guidelines. No excess toxicity or treatment related mortality was observed. Post-transplant MRI's showed no active disease. No patients with RRMS suffered relapse post-transplant, median reduction in EDSS scores was 2 at both 100 days (IQR 2) and at last follow up (IQR 2.5). EDSS scores stabilised in patients with SPMS. Conclusion: AHSCT is an effective treatment with acceptable toxicity in patients with aggressive, inflammatory MS.